2011
DOI: 10.1007/s12350-011-9355-2
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between myocardial perfusion imaging, coronary calcium score, and endothelial function in asymptomatic diabetics and controls

Abstract: Reversible perfusion defects and coronary calcium are more frequent in diabetics. CCS, abnormal endothelium-dependent vasodilation, and cholesterol/HDL ratio higher than 4, showed an association with perfusion abnormalities in asymptomatic diabetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
4
12
0
Order By: Relevance
“…Endothelial dysfunction may be considered as a cardiovascular risk factor or at least as a cardiovascular risk marker [12,25], but impairment of vascular smooth muscle cell function has been also reported in diabetic patients [9] and may be involved in altered FMD. The mechanism of impaired FMD cannot be explained in our results since we did not test specifically vascular smooth muscle cell function, like Peix et al [14]. The absence of significant difference between patients who constricted their brachial artery and those who did not for VCAM and albuminuria, which are usually considered as endothelium markers [26], might be consistent with the role of impaired smooth muscle cell function in our population.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Endothelial dysfunction may be considered as a cardiovascular risk factor or at least as a cardiovascular risk marker [12,25], but impairment of vascular smooth muscle cell function has been also reported in diabetic patients [9] and may be involved in altered FMD. The mechanism of impaired FMD cannot be explained in our results since we did not test specifically vascular smooth muscle cell function, like Peix et al [14]. The absence of significant difference between patients who constricted their brachial artery and those who did not for VCAM and albuminuria, which are usually considered as endothelium markers [26], might be consistent with the role of impaired smooth muscle cell function in our population.…”
Section: Discussionsupporting
confidence: 80%
“…When the cardiovascular risk profile of the patients was intermediate as in Peix et al . study (diabetes duration 11 years, age 58 years, hypertension, dyslipidemia and smoking habits in 77%, 73% and 32% of the patients, respectively), there was a higher prevalence of abnormal FMD in those with SMI as compared with those without, whereas no difference was found for the mean values of FMD [14]. As reported by Naka et al , duration of diabetes appears to be an important factor for developing impaired FMD [33].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our small study sample may have obscured any such possible association, nevertheless it should be kept in mind that diabetic complications do not have to follow a particular sequence. Our findings seem to be in line with those of Peix et al, (21) who showed that the presence of DM was the only predictor of abnormal myocardial perfusion and that total cholesterol/HDL ratio greater than 4 was correlated with perfusion abnormalities. In the DIAD study, where 522 diabetic patients were evaluated with adenosine MPI, an abnormal stress test result was not significantly associated with demographic characteristics, traditional cardiac risk factors, or laboratory variables (4).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have used different algorithms to identify diabetic patients who should or should not be referred for MPS. These algorithms have been based on numbers of traditional or emerging cardiovascular risk factors, the presence or absence of endothelium-dependent vasodilatation, the results of exercise ECG, or CAC score measurements [30,[85][86][87][88][89]. In particular, the presence of CAC is associated with a subsequent risk of cardiac events, with 1-99 Agatston units indicating low risk; 100-400 moderate risk; and [400 high risk [90].…”
Section: Which Diabetic Patients Should Be Referred For Mps?mentioning
confidence: 99%